Perception and Implementation of Agricultural Zakat by Rice Farming Communities (Case Study in Waringinsari Village, Langensari District, Banjar City): - Puji Nurnia; Shofiyulloh (Social Science Studies, 2022)
Zakat is a property that must be issued by Muslims, if the property has reached the haul and nishab. Agricultural zakat is plants, fruits, vegetables, grains such as rice, so it must be issued when it reaches the nishab, which is 653 kg of grain. And for the dose when issuing zakat, it is 10% if you rely on rainwater or springs only. And 5% is issued when irrigated with a tool, water from the river. This study aims to determine the extent to which the perception and implementation of the rice farming community in Waringinsari Village when paying or issuing zakat on their rice harvest. This study uses a qualitative method with primary data sources sourced directly through observations and interviews with informants of rice farming communities, secondary data sources are taken from data that has been stored by other people and documentation as complementary data. For data collection techniques, namely using observation, interviews, and documentation. The data analysis technique uses domain analysis, taxonomy, compensation, and cultural themes, with the research process after entering the field starting with determining reliable and authoritative informants, after that the researcher enters the interview stage to the informant and starts asking questions and then notes, after that The researcher asked descriptive questions followed by an analysis of the results of the interviews. The results of the research in Waringinsari Village show that the rice farming community understands that agricultural zakat must be issued if the harvest has reached the nishab. The community knows the existence of agricultural zakat through learning from recitations at the mosque. The implementation carried out by the community is that when issuing zakat, it is not according to the dose according to Islamic law but in a sincere way, and given directly to neighbors, orphans, the poor who are in the local community, no one has ever issued zakat on rice harvests through zakat institutions.